2021
DOI: 10.1002/jat.4160
|View full text |Cite|
|
Sign up to set email alerts
|

Alendronate reduces the cognitive and neurological disturbances induced by combined doses of d‐galactose and aluminum chloride in mice

Abstract: Neurological disturbances including cholinergic dysfunction, oxidative stress, neuroinflammation, and cognitive impairments are the well‐reported consequences of old age‐related disorders like Alzheimer's disease (AD) or dementia. Bisphosphonates were shown to ameliorate dementia in osteoporotic patients, neuroinflammation, and cholinesterase activity in rodents. Thus, the present study has been designed to examine the role of alendronate against cognitive and neurological disturbances in mice induced by a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The biochemical testing on the mice's liver and kidneys did not reveal any appreciable abnormalities. Previous findings (Khedr et al, 2022;Sumbalov a et al, 2022;Zameer et al, 2021;Zeng et al, 2022) were partially supported by the behavioural experiment results, which showed that the older mice were more sad, had worse motor function, and had worsened learning and memory capacities. After receiving Rg1 therapy, this circumstance became better.…”
Section: Discussionmentioning
confidence: 70%
“…The biochemical testing on the mice's liver and kidneys did not reveal any appreciable abnormalities. Previous findings (Khedr et al, 2022;Sumbalov a et al, 2022;Zameer et al, 2021;Zeng et al, 2022) were partially supported by the behavioural experiment results, which showed that the older mice were more sad, had worse motor function, and had worsened learning and memory capacities. After receiving Rg1 therapy, this circumstance became better.…”
Section: Discussionmentioning
confidence: 70%
“…These free radicals capture the electrons from surrounding biomolecules and create dysfunctions in cellular metabolism. [13] Our results indicate that the treatment of AlCl…”
Section: Nar Suppresses Alcl 3 -Induced Oxidative Stress In Different...mentioning
confidence: 60%
“…[11] Chronic exposure to aluminum generates free radical and reactive oxygen species (ROS) which interact with lipids and proteins of the cell membrane and cause elevation of LPO, PCO, and AOPP. ROS generation diminishes the activities of antioxidant enzymes (CAT, SOD and GR) and levels of GSH, [12,13] enhances the formation of NO [7] and the activity of acetylcholine esterase (AChE). [13,14] Thus, for the prevention and management of neurodegeneration, inhibition of oxidative stress and AChE targeting mechanisms are the greatest therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive dysfunction is the main expression of AD. d -galactose- and aluminum chloride-induced dementia model, a reliable animal model that resembles human dementia, has been widely used to screen anti-AD agents. , Aluminum chloride could induce neuronal inflammation and Aβ deposition in mice, resulting in learning and memory impairment. , In this study, we used an AD animal model induced with d -galactose and aluminum chloride to explore the effects of GB on AD. Recent studies have indicated that GB could ameliorate the learning and memory ability of vascular dementia rats .…”
Section: Discussionmentioning
confidence: 99%
“…The animals were randomized into three groups: Con group (control group), AD group (AD model group), and AD + GB group (GB-treated AD). The AD animal model was induced with d -galactose and aluminum chloride, according to previous studies. , Mice in the AD + GB group were intragastrically treated with 0.1% Ginkgolide B (Yuanye Biotechnology Co., Ltd. Shanghai, China) once daily for 2 weeks prior to the induction of AD, then intragastrically treated once daily for 2 weeks after the induction of AD. Mice in the AD and Con groups took the same amount of saline.…”
Section: Methodsmentioning
confidence: 99%